Interaksi Ekstrak Etanol Biji Nigella sativa Terhadap Bakteri Probiotik dan Patogen - Ahmad Shobrun Jamil (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2012)
Nigella sativa seed has a lot of beneficial health effect, such as immune-modulator, anti-histamine, anti-diabetic, anti-hypertension, anti-inflammatory, anti-microbes and antitumor. Numeral antimicrobial effect of Nigella sativa has been published, but only a few number of the information of the antimicrobial activity to the probiotic bacteria such as from the genus of Lactobacillus spp. However this research focused on the selectivity of the antimicrobial activity of N. sativa extract to the probiotic and pathogenic bacteria. This research begins with the extraction of N. sativa seed powder by ethanol 80% 1:3 (w/v). With rotary evaporator the macerates extracted till gained semi solid extract. In the other side probiotic and pathogenic bacteria broth cultures were prepared. Extract resoluted with concentration 5%; 2,5%; 1,25% and 0,625%. Into the extract were submerged some disk paper with 6 mm diameter. After that the disk put on to the solid medium were had cultured by bacteria then incubated overnight. The diameters of the clearing zone that seemed then measured. The result showing that the inhibitory zone occurred at 0,625% concentration. After general analysis there is no significant different inhibitory effect of the extract to the tested bacteria, but from the statistical analysis known that probiotik bacteria seemed more sensitive than pathogenic bacteria were tested.